(−)-Epigallocatechin-3-gallate (EGCG) prevents aminoglycosides-induced ototoxicity via anti-oxidative and anti-apoptotic pathways. (November 2021) - Zong, Yulong; Chen, Fang; Li, Shanshan; Zhang, Hui
Abstract: Objectives: Aminoglycoside-induced cochlear ototoxicity causes inner ear hair cells (HCs) loss and leads to hearing impairment in patients, but no treatment completely eliminates the ototoxic effect. This study aims to determine the effectiveness of (−)-Epigallocatechin-3-gallate (EGCG) as a protective agent against aminoglycoside-induced ototoxicity. Methods: Zebrafish were exposed to EGCG for 24 h and then co-treated with EGCG and ototoxic agent (amikacin and gentamicin) for 5 h to explore the protective effect of EGCG on zebrafish HCs. Network pharmacology analysis and molecular docking simulation were conducted to explore its potential mechanism, and in vitro cell experiments were used to validate the outcome of the result. Result: EGCG against ototoxicity of aminoglycosides in zebrafish HCs. Network pharmacology analysis and molecular docking showing that molecules related to cellular response regulation to oxidative stress, including AKT1, DHFR, and MET, may be the target proteins of EGCG, which were verified in vitro experiments. Further experiments demonstrated thatEGCG can antagonize the death of HCs caused by amikacin and gentamicin by reducing intracellular reactive oxygen species (ROS) accumulation and anti-apoptosis. Conclusion: EGCG can be an otoprotective drug against aminoglycosides-induced ototoxicity, prevent cellular apoptosis and significantly reduce oxidative stress.